El vínculo humano-animal y la fundamentación para la ética animal: temas para la bioética - Chaverri Suárez, Federico (2012)
This article broadly explores the relationship between humans and animals in Western society from biological and anthropological points of view. In addition, and within the same scope, it provides a historical summary of the philosophical discourse on the human-animal bond, concluding with a mention of the societal derivations that have stemmed from these historical processes.